Review of the 10 Most Disease Cases Based on Disease Type - Sartika Maulida Putri; Putri Maghfirah; Iriani Iriani; Yenni Fitri Velayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The reporting system is the presentation of data in the form of the results of activities in an organization as well as data from research results which are arranged systematically, so that it is easier to understand and easier to analyze and draw conclusions from an activity. The method in this research uses secondary data observation. The aim of this study was to determine the 10 most common diseases in outpatient and inpatient care (based on gender and age characteristics) at the Regional General Hospital, dr. Fauziah Bireun, This type of research is quantitative descriptive. The population and sample in this study are medical record recap data from January to December using total sampling. The results of the study showed that the highest number of diseases, namely Urolithiasis cases, had 314 outpatients, while the highest number of inpatients was Cerebral Infarction, there were 425 patients. There were 1,866 inpatients, based on the age range of 45-64 years, there were 1,042 outpatients and 958 inpatients. It is hoped that future researchers will carry out further research on the factors that cause health problems and health problems in patients with the highest cases of disease.